2013
DOI: 10.1103/physreve.88.023022
|View full text |Cite
|
Sign up to set email alerts
|

Electric-field-driven contact-line dynamics of two immiscible fluids over chemically patterned surfaces in narrow confinements

Abstract: We investigate the contact-line dynamics of two immiscible fluids in a narrow fluidic confinement comprising wettability-gradient surfaces, where the bulk fluid motion is actuated by an externally applied electric field. We assume that the channel walls bear spatially uniform surface potential. Our analysis, based on the diffuse interface formalism, reveals that the contact line undergoes stick-slip motion over the chemical patches and its velocity is a strong function of the interfacial electrokinetics. We al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 66 publications
1
39
0
Order By: Relevance
“…EDL has been shown 31,32 to play a very vital role in microscale transport processes and colloidal science. Recently, contact line motion of a binary fluid system actuated by a steady electric field has been addressed, 37 revealing the influence of various key parameters like EDL thickness and zeta potential on the dynamics of the contact line.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…EDL has been shown 31,32 to play a very vital role in microscale transport processes and colloidal science. Recently, contact line motion of a binary fluid system actuated by a steady electric field has been addressed, 37 revealing the influence of various key parameters like EDL thickness and zeta potential on the dynamics of the contact line.…”
Section: Introductionmentioning
confidence: 99%
“…The research investigations reported in the present paper are thus motivated by the question whether and how the density and viscosity contrasts alter the course of contact line motion, actuated by an external electric field in presence of EDL phenomena. To be precise, in the present study, we extend our prior work 37 in an effort to investigate the non-trivial effect of the contrast in fluid properties on the contact line dynamics. We highlight the profound influence of property contrasts of binary fluids and the surface wettability induced non-trivialities on the interfacial dynamics of contact line motion.…”
Section: Introductionmentioning
confidence: 99%
“…However, φ = 0 essentially represents a single isoline and indicates the nominal location of the interface of the binary fluid system. We use the following free energy functional to describe the thermodynamical behavior of the binary fluid system [7,12,18,22,[41][42][43]46,47]:…”
Section: Phase Field Modelmentioning
confidence: 99%
“…The ubiquities of the contact-line motion, relevant to many applications of these types, have attracted several researchers to concentrate on the underlying dynamical interactions over interfacial scales [5][6][7][8][9]. Furthermore, in recent years, the growing demand of miniaturization has necessitated the transport of small volumes of fluids in different physical processes, particularly, in chip cooling systems, on-chip biomedical analysis, drug delivery, and space technology.…”
Section: Introductionmentioning
confidence: 99%
“…In a numerical/experimental study, Lavi et al [6] showed that disregarding the effects of the inertia and the dynamic contact angle (i.e., the assumption made in the LW equation) leads to an inaccurate estimation of the capillary radius and the equilibrium contact angle. Mondal et al [7] investigated the effects of patterned wettability gradient and an external electric field on contact line dynamics of two immiscible fluids. They showed that the stick-slip motion velocity of the contact line (the rate of combined deformation behavior of semi-macroscopic contact region) is a strong function of the interfacial electrokinetics.…”
Section: Introductionmentioning
confidence: 99%